PENGGUNAAN SERAT SABUT KELAPA SEBAGAI BAHAN TAMBAH PADA CAMPURAN STONE MATRIX ASPHALT (SMA) – KASAR - Anwar, Iqbal Firdany; Desriantomy; Salonten; Purwantoro, Almuntofa (Jurnal Civil Engineering Study, 2024)
Advances in technology and science are anticipated to deal with the constraints associated with increasing the amount and quality of road construction, as well as road maintenance. Therefore, a construction technology for highway pavement layers that has been successfully developed in Germany since the 1960s, known as SMA S (Split Mastic Asphalt / Stone Matrix Asphalt with added Cellulose). This study was conducted with the aim of knowing the effect on the use of coconut fiber as a cellulose fiber additive in SMA (Split Mastic Asphalt / Stone Matrix Asphalt) type SMA mixtures. Determine the value of the Optimum Coconut Fiber Addition Rate and the value of the Marshall characteristics of the Stone Matrix Asphalt (SMA) mixture - Coarse using ex aggregate. Merak with varying levels of 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% The results of the research on the durability parameters of the Stone Matrix Asphalt (SMA) - Coarse mixture using the immersion test characteristic method for the Optimum Coconut Fiber Addition Level, the stability value decreases when it has been through immersion for 24 hours.